3D characterization and modeling of low cycle fatigue damage mechanisms at high temperature in a cast aluminum alloy. (15th January 2017) - Dezecot, Sebastien; Maurel, Vincent; Buffiere, Jean-Yves; Szmytka, Fabien; Koster, Alain
Abstract: Synchrotron X-ray tomography was used to monitor damage evolution in three dimensions during in situ Low Cycle Fatigue (LCF) tests at high temperature (250 °C) for an industrial material. The studied material is an AlSi7Cu3Mg aluminum alloy (close to ASTM A319) produced by Lost Foam Casting (LFC), a process which generates coarse microstructures but is nevertheless used for engine parts by the automotive industry. The volume analysis (3D images) has shown that cracks are extremely sensitive to microstructural features: coarse pores and hard particles of the eutectic regions are critical regarding respectively the main crack initiation and the crack growth. Finite Elements (FE) simulations, performed on meshes directly generated from 3D volumes and containing only pores, have revealed that mechanical fields also play a major role on the crack behavior. Initiation sites corresponded to areas of maximum inelastic strain while the crack path was globally correlated to high stress triaxiality and inelastic strain fields. Graphical abstract: Image 1